Protecting financial transactions through networks and point of sales. Issue 4 (1st October 2020) - Rizvi, Syed; Kurtz, Andrew; Williams, Iyonna; Gualdoni, Joseph; Myzyri, Ilva; Wheeler, Megan
ABSTRACT: Purchasing items on the Internet with a credit card can be extremely risky. To mitigate this risk, we propose a new Multi-Layer Defense (MLD) scheme which uses two-factor authentication by instituting a random number generator that is only valid for a preset amount of time. For two-factor authentication, we use an eight-digit code that serves as a redundant private key to authenticate the purchases. This can be utilized to identify users of credit cards and establish a more secure way of purchasing items via various marketplaces on the Internet. Specifically, the MLD scheme uses electronic devices to log into the credit card accounts via an application to view a randomly generated code. This is then inputted on an Online Retailer's website to authorize the use of the credit card. This ensures that a legitimate user is attempting to make a purchase and is not fraudulent. This redundancy, if used, can mitigate the circumstance of lost or stolen credit card information. The use of our proposed MLD scheme, specifically randomly generated code, when making a credit card purchase online could drastically cut down on fraudulent credit card purchases.